(untitled) (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2017)
Introduction. The open end of a coaxial line has good prospects of usage as a sensor for devices of flexi monitoring of parameters of materials in the microwave range. Its exact mathematical description requires the definition of the field in any section. Integral equation. A rigorous integral equation for the radial component of the electric field in the plane aperture is obtained. The technique of obtaining this equation is based on the method of partial areas and boundary conditions for magnetic components. The criteria of using the approximation of the given field and possibilities of the solution normalization are shown. Conclusions. The obtained technique can be distributed to solving problems a wide class of axissymmetric microwave devices. It is the basis of further analysis of their parameters and practical calculation. Information on the normalization summarize the results and will be useful in the selecting designs of sensors.